SISTEM INFORMASI RESERVASI KAMAR PADA HOTEL PALAPA TARUTUNG BERBASIS WEB - Jepryanta Natanael Brahmana; Jamaluddin Jamaluddin; Eviyanti Novita Purba (Universitas Methodist Indonesia, 2022)
Today's computer is a human need in completing various activities, combined with the presence of data innovation that is increasingly taking part in the realm of work. Utilizing the right data innovation instruments, it will create fast and precise data as needed so that choices can be made quickly. The design of making a Room Reservation Information System at the Palapa Tarutung Hotel is an element that greatly influences the smooth operation of the hotel's operational tasks. Information that is less-accurate, less efficient, and less effective can be solved by implementing this system. In the preparation of this final project, the author's goal is to simplify and speed up room reservations. The author uses PHP (Hypertext Processor Programming) as a programming language, Xampp is used to run the web server, and MySQL is used for database management which is currently quite in demand.